Expanding the application scope of on-farm biopurification systems: Effect and removal of oxytetracycline in a biomixture - Jiménez Gamboa, David (2017)
Antibiotic-containing wastewaters produced in agricultural activities may depress the pesticidedegrading capacity of biomixtures contained in biopurification systems. This work aimed to assay the effect of oxytetracycline (OTC) on the removal of carbofuran (CFN) in an optimized biomixture, and to determine the capacity of the system to dissipate OTC. During co-application of CFN + OTC, CFN removal and its accelerated degradation were not negatively affected. Similarly, different doses of OTC (10–500 mg kg−1) did not significantly affect CFN mineralization, and the process even exhibited a hormetic-like effect. Moreover, the biomixture was able to remove OTC with a half-life of 34.0 d. DGGEcluster analyses indicated that fungal and bacterial communities remained relatively stable during OTC application and CFN + OTC co-application, with similarities of over 70% (bacteria) and 80% (fungi). Overall, these findings support the potential use of this matrix to discard OTC-containing wastewater in this system originally intended for CFN removal.